Fabrication of a high tensile and antioxidative film via a green strategy of self-growing needle-like quercetin crystals in cassia gum for lipid preservation. (1st September 2020) - Cao, Lele; Feng, Huiyan; Meng, Fansong; Li, Jian; Wang, Lijuan
Abstract: Although active packaging materials have attracted many attentions, weak mechanical and barrier properties from active-ingredient addition need to be resolved. Here, a bio-degradable and anti-oxidative packaging film with a high tensile strength and a low permeability was prepared by self-growing needle-like quercetin in cassia gum solution during drying. Stereoscopic (SM) and scanning electron microscopy (SEM) showed that the quercetin was distributed evenly in needle-like ∼50-nm-diameter crystals in the film for an addition lower than 3.0%; and formed an urchin-like crystal when the addition was equal to or greater than 3.0% and the distribution was uneven. The needle-like quercetin crystal could enhance the mechanical and barrier properties, however, the urchin-like crystals contributed negatively. As quercetin dosage increased from 0% to 2.5%, tensile strength (TS) increased from 22.08 to 47.19 MPa, water vapor permeability (WVP) decreased from 2.16 to 1.45 g m −1 s −1 Pa −1 and oxygen permeability (OP) decreased from 1.69 to 1.20 cm 3  mm m −2 day −1, respectively. The composite film exhibited an excellent ultraviolet resistance and antioxidative performances for DPPH, ABTS +, HO and O2 - free radicals, and the corresponding scavenging activities were 80.07%, 92.15%, 124.42% and 96.92% in ethanol simulant, respectively. Its practical application in packaging pork lard showed that the cassia gum–quercetin film could delay oxidation and extend storage life. Therefore, the films prepared may provide guidelines for active packaging films that simultaneously with high mechanical and barrier properties. Graphical abstract: Image 1 Highlights: Cassia gum (CG)/quercetin composite films were prepared. Quercetin self-grew into ∼50-nm-diameter needle-like crystals at a proper dosage. The quercetin crystals contributed positively to mechanical and barrier properties. The film showed the high antioxidative performance and extend the lipid storage life.